Atelier Kempe Thill : new prototypes for a global society - Bookmakers vertalersteam Nijmegen; Atelier Kempe Thill; Kirkpatrick, John, ....-; Pepper, Ian, ....- (Rotterdam : 010, 2005)
For more information on Atelier Kempe Thill please visit: www.atelierkempethill.com <http://www.atelierkempethill.com > Exhibition Atelier Kempe Thill - Specific Neutrality: October 21st 2005 - December 23th 2005, Goethe-Institut, Westersingel 9, Rotterdam. At the heart of this publication is Atelier Kempe Thill's quest to find prototypes for a global society. How can buildings be made neutral and flexible as well as specific? It features realized work such as the Light Building (a travelling museum pavilion) and row houses in Roosendaal (NL) alongside recent plans including those for a youth hostel in the former Nazi resort at Prora in Germany, and the Franz Liszt Concert Hall in Raiding, Austria. It further includes a number of fascinating but unrealized schemes amongst which the winning design 'Living Inbetween' for Europan 5 Rotterdam and the competition entry for the Nam June Paik Museum in Korea. This book is published in conjunction with the award of the Rotterdam-Maaskant Prize for Young Architects 2005 to Oliver Thill.
[...]